Fire–Moisture Interactions Shape Recovery Trajectories Across Temperate Vegetation Communities - Emily K. Simpson; Glenda M. Wardle; Christopher R. Dickman; Aaron C. Greenville (Global Change Biology, 2026)
The recovery of vegetation following fire is increasingly shaped by concurrent climate‐driven hydrological extremes, such as drought and extreme precipitation. Under these multi‐disturbance scenarios vegetation communities are likely to show different recovery thresholds and trajectories of change, but this is yet to be fully understood or quantified. We used the Greater Blue Mountains World Heritage Area in south‐eastern Australia as a model system to assess how sustained moisture surplus or deficit could differentially influence the recovery of forest, heath and wetland vegetation from low‐extreme severity fire. From 2015 to 2024, this region experienced severe drought, extensive bushfires (the ‘Black Summer’ bushfires) and extreme rainfall events. By using a new remote‐sensing index (the Post‐fire Stability Index) that measures the rate of change in a disturbed system, we found that most vegetation communities could recover following low‐severity fire even in the case of poor soil moisture conditions, but moisture became increasingly limiting as burn severity increased. Certain communities, such as wet sclerophyll forests and freshwater wetlands, experienced disproportionate declines (up to times greater than other communities) as burn severity and drought intensified. These communities are likely at greatest risk as climate drying escalates. We stress that future recovery from fire in temperate communities will be governed not only by the characteristics of the fire itself and those of the affected vegetation community, but also by the extent to which these characteristics interact with prevailing hydro‐climatic conditions.